Letramentos Transculturais: internacionalização, mobilidade Discente e formação de professores de língua inglesa - José Alves Pereira Júnior (2017)
The present study investigated the phenomenon of the internationalization of higher education through international student mobility promoted by the Federal Univesity of Minas Gerais (UFMG). The internationalization, a strategy emergent from globalization, has placed upon higher education the need for implementing actions and practices pertaining to the Applied Linguistics field, area that originated this research. This study aimed at understanding the effects of the international experience of three English Language Teaching (ELT) students from the Faculty of Letters (FALE) who participated in the Minas Mundi Program. The aim was to problematize issues regarding the participants backgrounds, as well as their development of capital mobility strategies, and the impacts of international mobility on preservice teachers citizenship and professional education. The qualitative methodology chosen was the narrative inquiry. The choice of methods and instruments used by narrative inquiry for collecting and analyzing data made it possible to understand subjective aspects of the participants intercultural experience. The experiences shared by the three participants of the study enabled me to understand more about foreign language teaching and learning, as well as English teacher education, through their narratives. The analysis indicated that access to international mobility has promoted transforming effects to the pre-service teachers citizenship education and pedagogical practice construction. However, the results also indicated a need for rethinking internationalization actions and practices taken by the institution in order to facilitate even more the access of this student profile to international mobility programs. Those results showed the need for valuing the role of foreign language pre-service teachers in the promotion of necessary knowledge for the internationalization practices themselves.